Pengaruh Kepemimpinan terhadap Kinerja Karyawan pada Bank Desa Karawang - Suharyati, Anggie Angraini; Arnu, Anggi Pasca (Jurnal Ilmiah Wahana Pendidikan, 2025)
High employee performance can be achieved when every aspect of the organization is connected efficiently and can carry out their respective functions. In this research, this aspect refers to the leadership variable. Initial survey results show that employee performance has not yet reached optimal levels. The aim of this research is to identify the impact of leadership and work motivation on employee performance in the banking sector in Southeast Sulawesi. The method applied in this research is a descriptive and explanatory survey. Hypothesis testing uses the Structural Equation Model (SEM), while data processing is carried out using the LISREL 8.72 (Linear Structural Relationship) program. The findings from hypothesis testing show that both leadership and work motivation have a significant influence, both individually and simultaneously, on employee performance. This indicates that increasing the implementation of organizational leadership and work motivation can optimize the achievement of banking employee performance in Southeast Sulawesi.